Menjembatani Antara Misi Proselitisasi Islam-Kristen dan Keharusan Merawat Kerukunan:Konstruksi Teologis Forum Kerukunan Umat Beragama (FKUB) Kota Malang - Kholish, Moh. Anas; Rohmah, Siti (Islamic Insights Journal, 2020)
This study aims to determine and analyze the theological construction of Muslim and Christian religious leaders in FKUB Malang about the necessity of proselytizing mission on one side and the need to care for harmony on the other side. In addition, this study also seeks to explore how the strategic steps of Islamic and Christian leaders in FKUB Malang in bridging the necessity of the proselytizing mission and the need to care for harmony. This research is a qualitative research with a phenomenological approach. The results of this study are for FKUB Malang that the mission of proselytization in Islam and Christianity is a theological necessity. But in the process, it should not ignore the aspect of the plurality of Indonesian society which is also a theological necessity on the one hand and a sociological necessity on the other. So that for religious leaders in FKUB Malang, the necessity of proselytization which has the impact of inter-religious conflict must be avoided and prioritizes theology of peace building in a multicultural life. Because, the Principle of Love in the teachings of Jesus and the principle of al-salam in the teachings of Muhammad are universal principles in hacking religious conflicts that often occur in Indonesia. The proselytization strategy offered by religious leaders in FKUB Malang in building harmony among religious communities is to foster the quality of religious diversity of each adherent, as well as awareness of the heterogeneity of plural and inclusive communities in Malang. In addition, for Malang FKUB proselytizing efforts should not be made against people who are already religious. To realize this strategic effort, a redefinition of the interpretation of stray sheep which often becomes an exclusive and orthodox turbine driving force is needed.Keywords: Proselytization, Islam, Christianity, Caring for Harmony.